Impact of Ar:O2 gas flow ratios on microstructure and optical characteristics of CeO2-doped ZnO thin films by magnetron sputtering. (17th November 2021) - Sowjanya, M.; Shariq, Mohammad; Pilli, S. R.; Khan, M. Shakir; Alharbi, T.; Chaudhary, Anis Ahmad; Pamu, D.; Chowdharuy, R.; Fathy, A. M.; Slimani, Yassine; Imran, Mohd
Abstract: In this study, a radio frequency magnetron sputtering technique was applied to deposit eminently oriented ZnO thin films on stainless steel (SS316L). The effect of different ratios (Ar:O2 ) of gas flow ((20:0), (15:5), (10:10), (5:15), (0:20)) on optical and structural properties of CeO2 -doped ZnO thin films has been examined. The increase in grain size of thin films was observed with a partial increase in the Ar:O2 sputtering gas at substrate temperature of 673 K. The average surface roughness of the thin films has increased with sputtering gas. The photoluminescence peak exhibited a broad green-yellow band spiked at 467 nm for all the samples of CeO2 -doped ZnO thin films and a wide band of visible light focused in the 500–600 nm range. Intensity reduction of deep level emission peaks of ZnO films was observed. The refractive index of undoped and CeO2 -doped ZnO thin films with various sputtering gas ratios (Ar:O2 ) were also investigated. The optimized argon gas flow rate findings allow us to choose the deposition conditions for CeO2 -doped ZnO thin films for solar thermal applications.